STRATEGI MARKETING MIX DI PT. SEMEN INDONESIA PABRIK TUBAN - Fadali Rahman; Mad Yunus; Ahmad Nuruddin Hasbullah; Muhammad Sa’ud; Ainurrahman (ICO EDUSHA, 2022)
This research seeks to find out about marketing strategy at Semen Indonesia corporation. This study uses qualitative methods, with the type of case study research, in which data collection techniques are used in observation and documentation using primary and secondary data sources according to the research title. the discussion in this study is focused on marketing at Semen Indonesia corporation. Observations  ware carried out by participating in the kajlan program held by the research object. the resoult of this study provide information related to what kind of marketing planning is carried out by Semen Indonesia corporation as well as what are the parts in the marketing plan. References Alma, B. (2013). Menejemen Pemasaran Dan Pemasaran Jasa. Bandung: Alfabeta. Hidayat, Syarif. Semen: jenis & aplikasinya. Kawan Pustaka, 2009. Kotler. P., & Amstrong, G. (2016) Principle Of Marketing. New Jersey: Pearson Prentice Hall, Inc. Kotler. P., & Keller K. L. (2016). Marketing Menegemen (15 Ed.) New Jersey Pearson Prentice Hall, Inc. Kunaifi, Aang. Manajemen Pemasaran Syari’ah Pendekatan Human Spirit; Konsep, Etika, Strategi, dan Implementasi. 1 ed. Vol. 1. 1 1. Yogyakarta: Maghza Pustaka, 2016. Listyawati, Indri Hastuti. "Peran Penting Promosi dan Desain Produk Dalam Membangun Minat Beli Konsumen." Jurnal Bisnis, Manajemen, dan Akuntansi 3.1 (2016). Mubayyanah, Mubayyanah, Aang Kunaifi, Fadali Rahman, dan Abd Rosyid. “Ragam Menu, Harga, Dan Lokasi : Pengaruhnya Terhadap Loyalitas Pelanggan Restoran?” Masyrif: Jurnal Ekonomi, Bisnis dan Manajemen 1, no. 1 (2020): 148–74. http://dx.doi.org/10.28944/masyrif.v1i1.220. Purnama, Denta, and Aria Naufal Ardhana. "Tinjauan Atas Bauran Produk Pada Sekalikali Kopi." Jurnal Aplikasi Bisnis Kesatuan 1.2 (2021): 141-146. Riskiyah, Nuer, Aang Kunaifi, Matnin Matnin, dan Qaiyim Asyari. “Store Atmosphere Dalam Meningkatkan Keputusan Pembelian Pada Restoran Kapal Jodoh Batu Marmar Pamekasan.” Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam 8, no. 2 (28 Desember 2020): 54–62. https://doi.org/10.37812/aliqtishod.v8i2.158. Saputra, Taufik Aris, Aang Kunaifi, dan Siti Azizah. “Diversifikasi Produk Pendekatan Islamic Ethic Dalam Meningkatkan Omset Bisnis Retail.” Cendekia : Jurnal Studi Keislaman 7, no. 1 (2021): 1–16. Sagita, Rizka Alip, and Siswahyudianto Siswahyudianto. "Strategi Pemasaran Dalam Pengembangan Brand Awareness pada Sentra Olahan Salak Kunara Desa Kedungrejo Kecamatan Megaluh Kabupaten Jombang." INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia 5, no. 3 (2022): 327-340. Sstiyatik, Enni, and Beni Agus Setiono. "Pengaruh Product, Price, Promotion, dan Place Terhadap Loyalitas Konsumen." Jurnal Aplikasi Pelayaran dan Kepelabuhanan 10.1 (2019): 75-84. Suryanto, M. H., & SE, M. (2017). Metode Riset dan Analisis Saluran Distribusi. Gramedia Widiasarana Indonesia. Tjiptono,F. (2015). Strategi Pemasaran. Yogyakarta: Andi Willem J. Stantton, Prinsip Pemasaran, (Jakarta:Erlangga 1984)Jilid 1 Cet Ke 7 Hal. 207-307 Keywords: marketing mix, marketing strategy, Semen Indonesia Corporation